Infection by dry, airborne Botrytis cinerea conidia and fungicide efficacy on different parts of grape bunches and vinelets - Van Rooi, Cicelia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2002.